"Serial Drawing": A Therapeutic Approach with Young Children - Allan, John A. B. (Canadian Journal of Counselling and Psychotherapy, 2012)
The serial drawing technique is described and examples are used from two cases.With the moderately disturbed youngster, significant change tends to occur over ten sessions. The drawings often reflect a movement from initial feelings of violence, grief, loss of control and helplessness to self-disclosure of very painful experiences. Finally, feelings of growth, mastery and competence in relating to the outside world are manifested both in the drawings and improved behavior.